Pengaruh Profitabilitas, Likuiditas, Solvabilitas, Dan Kebijakan Dividen Terhadap Harga Saham: Studi pada perusahaan go public yang terdaftar dalam Indeks Kompas100 periode 2009-2011 - Pranata, Hans Christian; Kurnia, Ratnawati (Ultimaccounting Jurnal Ilmu Akuntansi, 2013)
The objective of this research is to examine the impact of profitability, liquidity, leverage, and also dividend policy partially and simultaneously towards share price. The profitability is proxied by Net Profit Margin (NPM), liquidity is proxied by Current Ratio (CR), leverage is proxied by Debt-to-Equity Ratio (DER), and dividend policy is proxied by Dividend Payout Ratio (DPR). The objects of this study are companies which have listed in Indeks Kompas100 in period 2009-2011. The samples are 17 companies determined based on purposive sampling. Data used in this study is secondary data such as financial statements and daily share price. The result of this study are (1) profitability proxied by Net Profit Margin has partial positive significant impact to share price (2) liquidity proxied by Current Ratio does not have partial negative significant impact to share price (3) leverage proxied by Debt-to-Equity Ratio does not have partial negative significant impact to share price (4) dividend policy proxied by Dividend Payout Ratio has partial positive significant impact to share price (5) profitability, liquidity, leverage, and dividend policy simultaneously have significant impact to share price. Keywords: profitability, liquidity, leverage, dividend policy, Net Profit Margin (NPM), Current Ratio (CR), Debt-to-Equity Ratio (DER), Dividend Payout Ratio (DPR), share price.